Highly Proton‐Conductive Zinc Metal‐Organic Framework Based On Nickel(II) Porphyrinylphosphonate. Issue 45 (1st July 2019) - Enakieva, Yulia Y.; Sinelshchikova, Anna A.; Grigoriev, Mikhail S.; Chernyshev, Vladimir V.; Kovalenko, Konstantin A.; Stenina, Irina A.; Yaroslavtsev, Andrey B.; Gorbunova, Yulia G.; Tsivadze, Aslan Y.
Abstract: The design of new solid‐state proton‐conducting materials is a great challenge for chemistry and materials science. Herein, a new anionic porphyrinylphosphonate‐based MOF (IPCE‐1Ni ), which involves dimethylammonium (DMA) cations for charge compensation, is reported. As a result of its unique structure, IPCE‐1Ni exhibits one of the highest value of the proton conductivity among reported proton‐conducting MOF materials based on porphyrins (1.55×10 −3  S cm −1 at 75 °C and 80 % relative humidity). Abstract : Easy and efficient ! A new porphyrinylphosphonate‐based MOF (IPCE‐1Ni ) was synthesized by an original synthetic approach. The crystal structure of the IPCE‐1Ni includes dimethylammonium cations localized in the pores, that determines the proton conductivity of 1.55×10 −3  S cm −1 at 75 °C and 80 % RH.